Antimicrobial resistance of isolated strains of Escherichia coli in BARF-type food for dogs in Lima, 2019 - Ortega Vassallo, Kiara (2021)
The aim of this study was to determine the presence of strains of Escherichia coli (E. coli) and antimicrobial resistance in BARF-type foods (Biologically Appropriate Raw Foods) for dogs, marketed in districts of Lima, Peru. In total, 124 samples of frozen raw diets belonging to 15 commercial brands were analysed, each sample from a different batch. The standard microbiological isolation was carried out using MacConkey and EMB culture media, and their identification through biochemical tests. For the serotyping of E. coli O157, a Latex test (Oxoid TSMX4147C) was used with latex particles sensitized with antibodies reactive to the somatic antigen O157, and for the identification of the H7 antigen, a similar specific Latex test (RIM E. coli O157: H7 Latex Test - Oxoid TSMX9410).The 65.3% (81/124; 95% CI: 56.9-73.7%) of the samples were positive for E. coli. Of the total colonies positive for E. coli, 38.2% were resistant to the 12 antimicrobials under study.